2019
DOI: 10.20944/preprints201909.0071.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive and Prognostic Factors in HCC Patients Treated with Sorafenib

Abstract: Sorafenib is an oral kinase inhibitor that enhances survival in patients affected by advanced hepatocellular carcinoma (HCC). According to the results of two registrative trials, this drug represents a gold quality standard in the first line treatment of advanced HCC. Recently, lenvatinib showed similar results in terms of survival in a non-inferiority randomized trial study considering the same subset of patients. Unlike other targeted therapies, currently predictive and prognostic markers in HCC patients tre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Drug therapy for HCC includes targeted drug therapy such as sorafenib, chemotherapy such as doxorubicin, and immunotherapy such as ICIs/monoclonal antibodies. 5-6,14 However, as HCC patients gradually become resistant to drugs, recent studies have tended to evaluate several clinical and biological markers and their mechanisms to improve the choice of patients suitable for treatment with these drugs. Numerous studies found that several lncRNAs have been involved in drug resistance in HCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drug therapy for HCC includes targeted drug therapy such as sorafenib, chemotherapy such as doxorubicin, and immunotherapy such as ICIs/monoclonal antibodies. 5-6,14 However, as HCC patients gradually become resistant to drugs, recent studies have tended to evaluate several clinical and biological markers and their mechanisms to improve the choice of patients suitable for treatment with these drugs. Numerous studies found that several lncRNAs have been involved in drug resistance in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…2 Sorafenib is a small-molecule oral multi-target tyrosine kinase inhibitor (TKI), which is the gold standard for first-line treatment authorized by U.S. Food and Drug Administration (FDA) for advanced liver cancer, which is difficult to operate on. 5 However, the prognosis of HCC patients treated with sorafenib remains poor due to its side effects and the patients’ increased resistance to the drug. 5,6 Studies have shown that the MAPK pathway and BRAF signaling play a vital role in regulating the proliferation and survival of HCC cells: TKI inhibitors exert their activity on HCC cells that inhibit BRAF signaling, and sorafenib can block the MAPK pathway-mediated signal transduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, 70–80% of patients cannot benefit from such opportunities because they are diagnosed at an advanced stage and can receive only palliative care. Sorafenib has been the standard choice for a decade in advanced HCC, even if other Tyrosine Kinase Inhibitors (TKIs) as well [4] are characterized by possible primary resistance or acquired resistance [5]. Recently, lenvatinib showed similar results in terms of survival in a non-inferiority randomized trial study considering the same subset of patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, 70%-80% of patients cannot benefit from such opportunities because they are diagnosed at an advanced stage and can receive only palliative care. Sorafenib has been the standard choice for a decade in advanced HCC, even if as well as other TKIs as well [4] is characterized by possible primary resistance or acquired resistance [5]. Recently, lenvatinib showed similar results in terms of survival in a non-inferiority randomized trial study considering the same subset of patients [6].…”
Section: Introductionmentioning
confidence: 99%